Volatile organic compounds (vocs) emitted from 40 mediterranean plant species:: Voc speciation and extrapolation to habitat scale (Atmospheric Environment, 2001)
Forty native Mediterranean plant species were screened for emissions of the C5 and C10 hydrocarbons, isoprene and monoterpenes, in ﬁve diﬀerent habitats. A total of 32 compounds were observed in the emissions from these plants. The number of compounds emitted by diﬀerent plant species varied from 19 (Quercus ilex) to a single compound emission, usually of isoprene. Emission rates were normalised to generate emission factors for each plant species for each sampling event at standard conditions of temperature and light intensity. Plant species were categorised according to their main emitted compound, the major groups being isoprene, a-pinene, linalool, and limonene emitters. Estimates of habitat ﬂuxes for each emitted compound were derived from the contributing plant species’ emission factors, biomass and ground cover. Emissions of individual compounds ranged from 0.002 to 505 g ha 1 h 1 (camphene from garrigue in Spain in autumn and isoprene from riverside habitats in Spain in late spring; respectively). Emissions of isoprene ranged from 0.3 to 505 g ha 1 h 1 (macchia in Italy in late spring and autumn; and riverside in Spain in late spring; respectively) and a-pinene emissions ranged from 0.51 to 52.92 g ha 1 h 1 (garrigue in Spain in late spring; and forest in France in autumn; respectively). Habitat ﬂuxes of most compounds in autumn were greater than in late spring, dominated by emissions from Quercus ilex, Genista scorpius and Quercus pubescens. This study contributes to regional emission inventories and will be of use to tropospheric chemical modellers